Development of PBL Powtoon Video Media for High School Student Learning Outcomes: Pengembangan Media Video PBL Powtoon untuk Hasil Belajar Siswa SMA - Sinaga, Rika Imelda; Tambunan , Hamonangan; Sitompul, Harun (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The integration of digital media in education has become essential in fostering effective learning, particularly in complex subjects such as economics. Specific Background: Project-Based Learning (PBL) models, when combined with animation, can enhance student engagement and comprehension. However, there is limited research on the development of Powtoon-based animated videos for specific economic topics. Knowledge Gap: Prior studies have not focused on animated media covering the topic of market and price equilibrium for high school economics, which often remains challenging and less engaging for students. Aims: This study aimed to develop, validate, and evaluate a Powtoon-based PBL animated video to improve students’ learning outcomes on this topic. Results: The media was declared feasible by experts (86%), practical by teachers and students (>89%), and effective in enhancing learning outcomes, with a moderate N-Gain score of 0.51 and statistically significant improvement in posttest results (p < 0.05). Novelty: This is the first validated digital learning tool focusing on market and price equilibrium using Powtoon within a PBL framework. Implications: The study supports the broader implementation of animated instructional media in economics education and encourages teacher training in digital pedagogy to meet 21st-century educational demands.Highlight : Developed a PBL-based animated video using Powtoon, validated as feasible and practical for classroom use. Experimental results show improved learning outcomes in economic topics like market equilibrium. Recommended for broader application and teacher training to enhance digital pedagogy. Keywords : Powtoon, project-based learning, animated video, economics education, learning outcomes